Renal functions in pediatric patients with beta-thalassemia major: relation to chelation therapy: original prospective study - ElMelegy Nagla T; Hamed Enas A (BMC, 2010)
Abstract Background In β-thalassemia, profound anemia and severe hemosiderosis cause functional and physiological abnormalities in various organ systems. In recent years, there have been few published studies mainly in adult demonstrating renal involvement in β-thalassemia. This prospective study was aimed to investigate renal involvement in pediatric patients with transfusion dependant beta-thalassemia major (TD-βTM), using both conventional and early markers of glomerular and tubular dysfunctions, and to correlate findings to oxidative stress and iron chelation therapy. Methods Sixty-nine TD-βTM patients (aged 1-16 years) and 15 healthy controls (aged 3-14 years) were enrolled in this study. Based on receiving chelation therapy (deferoxamine, DFO), patients were divided into two groups: group [I] with chelation (n = 34) and group [II] without chelation (n = 35). Levels of creatinine (Cr), calcium (Ca), inorganic phosphorus (PO4), uric acid (UA) and albumin were measured by spectrophotometer. Serum (S) levels of cystatin-C (SCysC) and total antioxidant capacity (STAC) and urinary (U) levels of β2-microglobulin (Uβ2MG) were measured by immunosorbent assay (ELISA). Urinary N-acetyl-beta-D-glucosaminidase (UNAG) activity and malondialdehyde (UMDA) were measured by chemical methods. Estimated glomerular filtration rate (eGFR) was determined from serum creatinine. Results In patient with and without chelation, glomerular [elevated SCysC, SCr, Ualbumin/Cr and diminished eGFR]; and tubular dysfunctions [elevated SUA, SPO4, UNAG/Cr, Uβ2MG/Cr] and oxidative stress marker disturbances [diminished STAC and elevated UMDA/Cr] were reported than controls. In patients with chelation, SCysC was significantly higher while, STAC was significantly lower than those without chelation. In all patients, SCysC showed significant positive correlation with SCr and negative correlation with eGFR; STAC showed significant positive correlation with eGFR and negative correlation with SCysC, SCr, UNAG/Cr; UMDA/Cr showed significant positive correlation with Ualbumin/Cr, Uβ2MG/Cr, UNAG/Cr. Conclusions Our data confirm high frequency of glomerular and tubular dysfunctions in TD-βTM pediatric patients which could be attributed to oxidative stress and DFO therapy.